Preparation of SiC-based composites by cold isostatic press - Harun, M. B.; Halim, M. H.; Yazid, H.; Selamat, Z.; Sattar, M. S.; Jali, M. (American Institute of Physics, 2010)
Link to publisher's homepage at www.aip.org/